A new Moodle module supporting automatic verification of VHDL-based assignments - Gutiérrez, Eladio; Trenas, María A.; Ramos, Julián; Corbera, Francisco; Romero, Sergio (Computers and education, 2010)
This work describes a new Moodle module developed to give support to the practical content of a basic computer organization course. This module goes beyond the mere hosting of resources and assignments. It makes use of an automatic checking and verification engine that works on the VHDL designs submitted by the students. The module automatically keeps up to date information about their state, and significantly reduces the overload that a continuous assessment demands to the teacher. Additionally, this new module is oriented to promote a collaborative teamwork allowing to define student teams in a more operative way than built-in Moodle groups. The module has been designed according to the Moodle philosophy and its application can be extended to other similar subjects.